2016
DOI: 10.1007/s11243-016-0049-0
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, crystal structures and in vitro anticancer activities of oxovanadium(IV) complexes of amino acid Schiff base and 1,10-phenanthroline ligands

Abstract: Four oxovanadium(IV) complexes, namely [VO(desa-met)(phen)]ÁMeOHÁ2H 2 O (1) (desa-met = Schiff base derived from 4-(diethylamino)salicylaldehyde and DLmethionine, phen = 1,10-phenanthroline), [VO(o-van-met)-(phen)]ÁMeOHÁCH 2 Cl 2 Á3H 2 O (2) (o-van-met = Schiff base derived from o-vanillin and DL-methionine), [VO(dtbsnapa)(phen)]Á2H 2 O (3) (dtbs-napa = Schiff base derived from 3,5-di-tert-butyl salicylaldehyde and 3-(1-naphthyl)-Lalanine) and [VO(hyna-napa)(phen)]Á1.5H 2 O (4) (hynanapa = Schiff base derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…This complex can be replaced with oxygen to form oxyhemoglobin and maintain normal physiological functions in organisms [ 25 ]. In addition, studies on the biological activities of essential metal complexes, such as antimicrobial, antiphlogistic, oxidation resisting, antidiabetic, and antineoplastic, have aroused the interest of scientific researchers [ 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…This complex can be replaced with oxygen to form oxyhemoglobin and maintain normal physiological functions in organisms [ 25 ]. In addition, studies on the biological activities of essential metal complexes, such as antimicrobial, antiphlogistic, oxidation resisting, antidiabetic, and antineoplastic, have aroused the interest of scientific researchers [ 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only V‐33 and V‐34 were found to have weak anticancer activity towards A‐549 and Hep‐G2 cells with IC 50 values of 28.4 to 45.2 μmol L −1 . Furthermore, the activity of these complexes was shown to be lower than the cisplatin and VO(acac) 2 controls [94] (Figure 8, Table 6).…”
Section: Complexes With Tridentate Schiff Bases O N O With Metals Of ...mentioning
confidence: 99%
“…2 The crystal structures of complexes involving the Schiff base derived from salicylaldehyde and amino acids revealed that the Schiff base ligands mainly act as tridentate ligands, coordinating through the phenolato oxygen, imine nitrogen and carboxylate oxygen. [3][4][5] Supramolecular architectures with coordination bonds, hydrogen bonds and π-π stacking interactions have received much attention for its prospective applications in the elds of host-guest chemistry, biochemistry, electronics, magnetism, optics, gas absorbent, catalysis and molecular recognition. [6][7][8][9] These interactions are becoming increasingly important in supramolecular chemistry and crystal engineering.…”
Section: Introductionmentioning
confidence: 99%